2020
DOI: 10.3389/fmicb.2020.00318
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and Functional Characterization of Culturable Endophytic Actinobacteria Associated With Camellia spp. for Growth Promotion in Commercial Tea Cultivars

Abstract: Plant associated endophytic actinobacteria may contribute to plant growth and defense by direct or indirect methods. Our aim was to evaluate the plant growth promoting and antifungal activities of endophytic actinobacteria associated with Camellia spp. and related genera, Eurya to find potent plant growth promoting strains that could be applied in future microbe based bioformulations. We isolated 46 endophytic actinobacteria based on morphological characteristics of the isolates. 16S rRNA gene sequence analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 77 publications
4
33
0
Order By: Relevance
“…In this study, three actinobacterial strains were able to effectively produce endoglucanases. Similarly, several previous studies have reported that actinobacteria in the genera Actinoalloteichus, Actinoplanes, Amycolatopsis, Arthrobacter, Cellulomonas, Kitasatospora, Micromonospora, Mycobacterium, Nocardia, Nocardioides, Rhodococcus, Saccharomonospora, Streptomyces, Streptosporangium, and Thermomonospora could produce cell-wall degrading enzymes, especially endoglucanases [61,[64][65][66].…”
Section: Discussionmentioning
confidence: 69%
“…In this study, three actinobacterial strains were able to effectively produce endoglucanases. Similarly, several previous studies have reported that actinobacteria in the genera Actinoalloteichus, Actinoplanes, Amycolatopsis, Arthrobacter, Cellulomonas, Kitasatospora, Micromonospora, Mycobacterium, Nocardia, Nocardioides, Rhodococcus, Saccharomonospora, Streptomyces, Streptosporangium, and Thermomonospora could produce cell-wall degrading enzymes, especially endoglucanases [61,[64][65][66].…”
Section: Discussionmentioning
confidence: 69%
“…Actinobacteria can promote plant growth by making nutrients/substrates (e.g., phosphorous, nitrogen, and iron) accessible to the host plant and producing various plant hormones ( Liu et al, 2017 ; Purushotham et al, 2018 ; Borah & Thakur, 2020 ). IAA is an important plant hormone beneficial to plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that the root-associated actinobacteria contribute to plant growth promotion ( Dutta & Thakur, 2020 ), and plant stress alleviation ( Esmaeil Zade, Sadeghi & Moradi, 2018 ; Selim et al, 2019 ), through diverse mechanisms such as indole-3-acetic acid (IAA) biosynthesis, siderophore production, and phosphate solubilization. Studies have investigated the impact of actinobacteria on plant growth promotion and seed germination rate improvement ( Zamoum et al, 2015 ; Allali et al, 2019 ; Borah & Thakur, 2020 ). Also, actinobacteria ability to mitigate the negative impact of abiotic stress on the growth and physiology of crops, such as wheat ( Yandigeri et al., 2012 ; Li et al, 2019 ), maize ( Warrad et al, 2020 ), tomato ( Abbasi, Sadeghi & Safaie, 2020 ) has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…As a primary example, polyketide synthases (PKSs) and nonribosomal peptide synthetases (NRPSs), which are multifunctional enzyme systems that assemble many of the secondary metabolites from simple building blocks including carboxylic acids and amino acids [202,203], show limited expression under laboratory conditions [204]. Extensive efforts have been made to unsilence such clusters [205,206]. Most genetic manipulation methods attempting to control PKSs and NRPSs as multifunctional enzymes to regulate expression of BGCs rely on multi-target approaches not specific to a single secondary metabolite and display complex interactions.…”
Section: Isolation Is the Problemmentioning
confidence: 99%